2007
DOI: 10.1080/00016340601034970
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual disorders and associated factors among adolescent girls visiting a youth clinic

Abstract: We found hypothalamic amenorrhea and hyperandrogenism to be frequent endocrine mechanisms of menstrual disorders in teenagers. Concomitant eating disorder was highly frequent and secondary amenorrhea was associated with anorectic behavior. It is important to evaluate endocrine patterns and eating behavior in adolescents with menstrual disturbances to ensure adequate medical care and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…There are several etiologies for menstrual disturbances in the perimenarchal years, including immaturity of the hypothalamicpituitary-ovarian axis resulting in anovulatory cycles, polycystic ovary syndrome, anorectic eating patterns, over-exercising and pregnancy. 6 A thorough history and examination will help to elucidate some of these causes and direct appropriate investigations. In our practice, a HEADSS screen is routinely undertaken in order to determine any health-risk behaviors that may be contributing to the presenting problem.…”
Section: Discussionmentioning
confidence: 99%
“…There are several etiologies for menstrual disturbances in the perimenarchal years, including immaturity of the hypothalamicpituitary-ovarian axis resulting in anovulatory cycles, polycystic ovary syndrome, anorectic eating patterns, over-exercising and pregnancy. 6 A thorough history and examination will help to elucidate some of these causes and direct appropriate investigations. In our practice, a HEADSS screen is routinely undertaken in order to determine any health-risk behaviors that may be contributing to the presenting problem.…”
Section: Discussionmentioning
confidence: 99%
“…46 All types of eating disorders are associated with an increased risk of menstrual dysfunction, and one study showed that "different types of eating disorders" were found in 68% of amenorrheic adolescents and 38% of oligomenorrheic adolescents. [47][48][49] …”
Section: Menstrual Dysfunctionmentioning
confidence: 99%
“…Physiological variations as well as social and psychological factors that differ across cultures influence the prevalence of reproductive problems and medical help-seeking behavior [1] . Although 'race' or ethnicity are commonly used variables in medical research [2] and many studies have attempted to assess health behaviors related to geographical or cultural factors [3][4][5] , previous cross-cultural research on these issues has focused on women of European descent or on women from other cultures living in Western countries [3,6] . To date, there are limited data on these issues regarding women from Asian countries.…”
Section: Introductionmentioning
confidence: 99%